2011
DOI: 10.1038/hr.2011.136
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren in combination with valsartan exerts synergistic protective effects against ventricular remodeling after myocardial infarction in mice

Abstract: The efficacy of aliskiren, a direct renin inhibitor, in ventricular remodeling after myocardial infarction (MI) compared with conventional renin-angiotensin system (RAS) inhibitors remains to be defined. This study was performed to examine the protective effects of aliskiren and its addition to valsartan, an angiotensin-II receptor blocker, against ventricular remodeling after MI. MI was induced in 8-to 12-week-old C57BL/6 mice by ligating the left anterior descending artery. At 3 days after MI, mice were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…Gervais and colleagues showed that treatment with valsartan at 50 mg/kg/day, given from day 7 post-MI for 6 weeks, limited the development of cardiac hypertrophy in Wistar rats [24]. Higashikuni et al showed that, in mice, valsartan at 25 mg/kg/day, given from 3–28 days post MI, ameliorated ventricular remodeling [25]. The previous studies and our own data suggest that the dosage and the timing of treatment have significant and differential effect on LV remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Gervais and colleagues showed that treatment with valsartan at 50 mg/kg/day, given from day 7 post-MI for 6 weeks, limited the development of cardiac hypertrophy in Wistar rats [24]. Higashikuni et al showed that, in mice, valsartan at 25 mg/kg/day, given from 3–28 days post MI, ameliorated ventricular remodeling [25]. The previous studies and our own data suggest that the dosage and the timing of treatment have significant and differential effect on LV remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Aliskiren could be involved in inhibition of the rennin receptor internalization and, as a consequence, prevent AngII-independent signaling pathway and its deleterious consequences. Most recent studies demonstrated that in combination with the inhibitor of angiotensin converting enzyme or AngII receptor blocker, aliskiren exerted additional synergistic protective effects against ventricular remodeling following myocardial infarction in rodents [32, 33] although clinical trials demonstrated no additional benefit of RAS blockade with aliskiren in post-infarcted patients [34]. The beneficial effects of combined therapy could indicate existence of AngII-independent pathways through which aliskiren would affect cell metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies documenting the potent anti-inflammatory potential of aliskiren through inhibiting leukocyte adhesion, preventing oxidative stress and decreasing the production of inflammatory cytokines including TNF-a. 13,33,34 Furthermore, aliskiren has also been shown to attenuate TNF-a mediated deleterious effects on different body systems including the coagulation pathway in human umbilical vein endothelial cells. 34 An aliskiren-induced decrease in inflammatory mediators in the present study may possibly be due to a decrease in angiotensin II levels as this has been well documented to modulate several steps of the inflammatory response including vascular permeability, leukocyte infiltration, production of reactive oxygen species and inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%